New hopes and challenges in targeted therapy and immunotherapy for primary central nervous system lymphoma - Yang, Chuanwei; Ren, Xiaohui; Cui, Yong; Jiang, Haihui; Li, Ming; Yu, Kefu; Shen, Shaoping; Li, Mingxiao; Zhang, Xiaokang; Zhao, Xuzhe; Zhu, Qinghui; Bu, Xingyao; et al. (Frontiers in Immunology, 2025)
Primary central nervous system lymphoma (PCNSL) is non-Hodgkin’s lymphoma (NHL) confined to the central nervous system. Most of the patients eventually develop relapsed/refractory (R/R) PCNSL, and the overall prognosis for PCNSL remains dismal. Recently, gene sequencing, transcriptome sequencing, and single-cell sequencing platforms have provided a large amount of data revealing the mechanisms underlying the pathogenesis and drug resistance in PCNSL, including the activation of the NF-κB signaling pathway in tumor cells, tumor heterogeneity, and the immunosuppressive tumor microenvironment. Advances in molecular pathology studies for PCNSL have led to identifying new therapeutic targets and developing novel drugs. New therapeutic strategies, such as creating small molecule targeted agents, immunomodulatory drugs, immune checkpoint inhibitors, and chimeric antigen receptor T (CAR-T) cell therapy, have brought new hope for patients with PCNSL, especially for R/R PCNSL. This review presents recent advances in the treatment of PCNSL, reviews and discusses the efficacy and challenges of targeted therapy and immunotherapy, and provides an outlook on the future development of PCNSL treatment strategies.